A Comparison of learning gains when using a 2D simulation tool versus a 3D virtual world: An experiment to find the right representation involving the Marginal Value Theorem. (August 2015) - Richards, Deborah; Taylor, Meredith
Abstract: The use of three-dimensional Virtual Worlds in the classroom offers the promise of engaging and authentic learning experiences. Given the effort and investment involved in the creation of these worlds, more studies are needed which measure the learning gains. In particular, greater understanding is needed concerning what aspects of the technology are beneficial for learning what sort of content and in what context. We conducted two experimental studies involving 129 biology students over a two-year period that sought to make a contribution towards this understanding. Our study compared the knowledge of students after a traditional classroom lecture about a biological theorem known as Marginal Value Theorem, with their knowledge after they were exposed to simulations of two-dimensional models developed in NetLogo and three-dimensional models developed in Unity3D. Perhaps due to cognitive overload and distractors in the virtual world, it appears that the two-dimensional NetLogo model delivered better learning outcomes. Highlights: Cost-benefit analysis of 3D virtual worlds over alternative learning methods and representations is scarce. In two separate studies, 129 biology students explored an animal behaviour theory in six scenarios represented in 2D and 3D. Posttests measured learning gains compared to a pretest following traditional classroom presentation of the theory. 2D simulations were modelled in NetLogo and 3D simulations used Unity3D. Perhaps due to cognitive overload and distraction-conflict theory, 2D Netlogo delivered better learning outcomes.